Poetry and philosophy in the Middle Ages: a festschrift for Peter Dronke - Marenbon, John; Dronke, Peter (Mittellateinische Studien und Texte 0076-9754, 2010)
This collection of essays, written to honour Professor Peter Dronke on his retirement, addresses the question of the relationship between poetry and philosophy in the Middle Ages